2006
DOI: 10.1111/j.1365-2400.2006.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of different structures to age freshwater fish from a northeastern US river

Abstract: Largemouth bass, Micropterus salmoides (Lacepe`de), smallmouth bass, Micropterus dolomieu Lacepe`de, and yellow perch, Perca flavescens (Mitchill), were collected from the Hudson River, New York, USA, to compare the precision of age estimates derived from scales and otoliths. Similar procedures were used to compare otolith and spine ages from brown bullhead, Ameiurus nebulosus (Lesueur). Overall percent agreement between readers ranged from 91% to 98% for otoliths compared with 38% to 67% for scales and spines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 18 publications
8
79
0
1
Order By: Relevance
“…Thus, longevity of largemouth bass and yellow perch in the upper Hudson River was similar to longevity of these species in other water bodies of the same latitude. As far as we know, published otoliths ages for brown bullheads have only been reported from the upper Hudson River (Maceina and Sammons, 2006). However, Rypel (2011) examined age data, presumably from sectioned spines, from 35 North American brown bullhead populations and reported maximum ages of 10 to 16 years old, similar to our observations from the Hudson River.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, longevity of largemouth bass and yellow perch in the upper Hudson River was similar to longevity of these species in other water bodies of the same latitude. As far as we know, published otoliths ages for brown bullheads have only been reported from the upper Hudson River (Maceina and Sammons, 2006). However, Rypel (2011) examined age data, presumably from sectioned spines, from 35 North American brown bullhead populations and reported maximum ages of 10 to 16 years old, similar to our observations from the Hudson River.…”
Section: Discussionsupporting
confidence: 85%
“…From 2003 to 2005, all sizes (>age 1) of yellow perch and largemouth bass were collected with DC electrofishing along pre-established transects in each pool as described by Maceina and Sammons (2013). Table A1), a subsample of all fish collected were aged with otoliths using the procedures described by Buckmeier et al (2002) and Maceina and Sammons (2006). Fish collection and processing followed applicable USEPAapproved standard operating procedures.…”
Section: Fish Collection and Processing For Agingmentioning
confidence: 99%
“…Comparison of age estimates from various ageing structures have been reported to be undertaken in a number of fishes with a view to identify the most suitable structure for a fish population (Reid, 2007;Phelps et al, 2007;Maceina and Sammons, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it is possible that ages estimated from scales inaccurately measured actual fish age, particularly of older individuals. Maceina and Sammons (2006) reported that age estimates derived from largemouth bass scales from the Hudson River, NY, typically overestimated fish ages relative to otoliths for ages 1À9, and then underestimated ages relative to otoliths for age-10þ individuals. We observed relatively few individuals age-10 and older (3, 1, and 3 for Hemlock Reservoir, Easton Reservoir, and Mansfield Hollow Reservoir, respectively); however, the extent to which underestimation of fish ages may have affected our results is unknown.…”
Section: Discussionmentioning
confidence: 99%